Discontinuous Galerkin method for coupling hydrostatic free surface flows to saturated subsurface systems. (1st May 2019) - Reuter, Balthasar; Rupp, Andreas; Aizinger, Vadym; Knabner, Peter
Abstract: We formulate a coupled surface/subsurface flow model that relies on hydrostatic equations with free surface in the free flow domain and on Darcy's law in the subsurface. The model is discretized using the local discontinuous Galerkin method, and a statement of discrete energy stability is proved for the fully non-linear coupled system. The performance of the proposed scheme is illustrated by a numerical convergence study and a realistic example.